A Contemporary Approach to the Oldest International Crime. Issue 84 (12th April 2017) - Scharf, Michael; Taylor, Mistale
Maritime piracy began to re-emerge a decade ago, mostly off the coast of Somalia, thereby presenting major economic, security and humanitarian concerns. Prosecuting piracy raises many issues, not in the least because traditional maritime piracy from 200 years ago is so notably different from contemporary piracy. The present article describes the Public International Law and Policy Group's formation of the High Level Piracy Working Group (HLPWG), which since 2011 has been producing memoranda on major issues in contemporary piracy prosecution. The issues span the legal foundations of piracy prosecution, including how to criminalise certain acts and how to exercise jurisdiction over such acts. Laws governing the use of force could apply to government or private actors when capturing and apprehending pirates. Once captured, there are questions of extraditing and transferring these pirates. Moreover, when such pirates are eventually brought to trial, there are pre-trial, evidentiary, substantive and post-prosecution issues to consider. The article also explores the merits and likelihood of creating an international piracy court. It shows how the HLPWG has influenced legal and policy developments today that draw on the distant past, and will undoubtedly have an enduring legacy in the future.